"Turn-on" fluorescent sensor for oleanolic acid based on o-phenyl-bridged bis-tetraphenylimidazole. (1st September 2023) - Wu, Hanqing; Zheng, Linlu; Lin, Liangbin; Guo, Hongyu; Yang, Fafu
Highlights: New fluorescence sensor based on bis-tetraphenylimidazole (PTPI ) was synthesized. PTPI showed on-site sensing selectivity for oleanolic acid with "turn-on" fluorescence. The detecting limitation of PTPI for oleanolic acid was 0.032 μM. PTPI detected oleanolic acid in real samples with recoveries of 96.0%–106.0%. The detecting mechanism was clarified as 1:1 binding stoichiometry. Abstract: Fluorescent sensors had been extensively applied on sensing various biomolecules effectively, but no fluorescent sensor for oleanolic acid was presented up to now. In this work, the first fluorescent sensor for oleanolic acid was designed and synthesized based on o-phenyl-bridged bis-tetraphenylimidazole (PTPI ). PTPI was prepared by bridging two tetraphenylimidazole units and o-phenylenediamine via Schiff-base condensation in yield of 86%. PTPI showed high sensing selectivity for oleanolic acid among 26 biomolecules and ions. The blue fluorescence at 482 nm was enhanced by 4.5 times after sensing oleanolic acid in aqueous media. The fluorescence sensing ability of PTPI for oleanolic acid maintained stable in pH = 5–9. The detecting limitation was as low as 0.032 μM. The detecting mechanism was clarified as 1:1 binding stoichiometry by fluorescence Job's plot, mass spectrometry, 1 H nuclear magnetic resonance and fourier transform infrared spectroscopy. The detecting ability of PTPI for oleanolic acid was successfully used for paper test and real samples of grapes and Kuding tea with recoveries in the range of 96.0%-106.0%, indicating the good application potential for on-site detecting oleanolic acid in real samples of fruits and food.